SHOP-Net: Moving from Paper to Mobile - Talbot, Michael (Department of Statistical Sciences, 2024)
Stock-ordering is one of the challenges that microenterprises face, because shop owners often need to leave their shops to travel to suppliers of goods. Triple Trust Organization (TTO) is a non-profit organization (NGO) that works with microenterprises around Cape Town and addresses this problem. They act as a supplier and fetch stock orders from shops they work with. Their ordering system relied on paper order forms and had a number of inefficiencies. To address these inefficiencies, a mobile-based stock-ordering system was designed with TTO. This system allows orders to be recorded and sent to a server at the TTO office using a mobile phone application where the orders are then processed. This system successfully increased TTO's efficiency in three ways, namely, improved data processing ability, increased order accuracy and increased access to information. The evaluation was done according to their success criteria and the system has been in use for seven months. We argue that evaluations with NGOs should go further than just the management but include all of those affected by the system.